A green tea extract catechin EGCg: Therapeutic potential for pediatric cardiomyopathies - Junjun Quan; Dustin Gerber; Ang Li; Xupei Huang; Jie Tian (Wiley, 2023)
Abstract Cardiomyopathies comprise a group of disorders wherein the primary defect is in cardiac myocytes. The common forms of pediatric cardiomyopathies, classified according to their morphological and functional manifestations, include dilated cardiomyopathy (DCM), restrictive cardiomyopathy (RCM), hypertrophic cardiomyopathy (HCM), and others. Cardiac gene mutations caused abnormal myofibril Ca2+ sensitivity may be involved in the underlying molecular mechanisms of cardiomyopathies. Thus far, no effective treatment for cardiomyopathies has been developed, especially for HCM and RCM in which diastolic dysfunction occurs early and followed by diastolic heart failure. Our laboratory is among the first in the field to investigate the mechanisms underlying various cardiomyopathies and search for the treatment for these disorders. In the past, we and other researchers have found that (−)‐epigallocatechin‐3‐gallate (EGCg), the major biomedical polyphenol extracted from green tea, possess multiple therapeutic effects on protecting cardiac function and correcting impaired relaxation. Given its therapeutic effects, EGCg might be a potential drug candidate for administration to patients with cardiomyopathy and heart failure. In this review, we will discuss the molecular mechanisms associated with the pathogenesis of diastolic dysfunction and summarize the pharmacological effects of EGCg on experimental animals and pediatric patients with cardiomyopathies and diastolic dysfunction.